MicroRNAs targeting Nicastrin regulate Aβ production and are affected by target site polymorphisms - Delay, Charlotte; Dorval, Véronique; Fok, Alice; Grenier-Boley, Benjamin; Lambert, Jean-Charles; Hsiung, G.-Y.; Hébert, Sébastien S. (Frontiers in Molecular Neuroscience, 2014)
Despite the growing number of genome-wide association studies, the involvement of polymorphisms in microRNA target sites (polymiRTS) in Alzheimer’s disease (AD) remains poorly investigated. Recently, we have shown that AD-associated single nucleotide polymorphisms (SNPs) present in the 3’untranslated region (3’UTR) of Amyloid precursor protein (APP) could directly affect miRNA function. In theory, loss of microRNA (miRNA) function could lead to risk for AD by increasing APP expression and Aβ peptide production. In this study, we tested the hypothesis that Nicastrin, a γ-secretase subunit involved in Aβ generation, could be regulated by miRNAs, and consequently affected by 3’UTR polymorphisms. Bioinformatic analysis identified 22 putative miRNA bindings sites located in or near Nicastrin 3'UTR polymorphisms. From these miRNA candidates, six were previously shown to be expressed in human brain. We identified miR-24, miR-186 and miR-455 as regulators of Nicastrin expression, both in vitro and under physiological conditions in human cells, which resulted in altered Aβ secretion. Using luciferase-based assays, we further demonstrated that rs113810300 and rs141849450 SNPs affected miRNA-mediated repression of Nicastrin. Notably, rs141849450 completely abolished the miR-455-mediated repression of Nicastrin. Finally, the rs141849450 variant was identified in 1 out of 511 AD cases, but not in 631 controls. These observations set the stage for future studies exploring the role of miRNAs and 3’UTR polymorphisms in AD.